ARGUMENTASI TEOLOGIS TENTANG DAMPAK DOSA TERHADAP PIKIRAN - Riswan Ramasin; Fasmani Ndruru (Phronesis: Jurnal Teologi dan Misi, 2022)
The mind, which is unique to man, is inseparable from sin after the fall into sin. Empiricists who always take the experience as the measure of human life reject this impact with the view that, although humans are mortal, humans are morally neutral. The impact of sin on the mind is that man cannot find the truth with his reason, but he always fails to do so. The death of the human spirit causes horrors that are incredibly disgusting and grieve the heart of God. However, worldly man does not care about all that but is proud of the sins and injustices he has committed. The discussion on this topic is presented descriptively based on theological arguments according to the views of several experts summarised in a prescriptive presentation. As a result, sin has made all aspects of human life experience terrible things. Three aspects are affected by the sinful mind, namely, "man no longer recognizes his existence as a creature of God (Spiritual Aspect), Man becomes a crisis of goodness and is unlikely to seek God (Moral Aspect), and man is younger to misunderstand, faster to judge and prefers to be alone than to associate with others (social aspect).